Successive-Stage Speed Limit on Exit Ramp Upstream of Direct-Type Freeway in China - Hongwei Li; Jian Lu; Yongfeng Ma; Yuanlin Liu (Discrete Dynamics in Nature and Society)
The first objective of this study is to analyze a successive-stage speed limit model developed for vehicles along the exit upstream ramp of direct-type freeway in China. This paper (1) explains the necessity to implement speed limit to the exit ramp upstream, (2) analyzes whether speed limit is related to the length of the deceleration lane, vehicle type, saturation, and turning ratio and (3) proposes a speed prediction model and calibrates speed-limit sign validity model and establishes successive-stage speed limit model. The results. Δν85≥10 illustrates the necessity of the using speed limit on the exit ramp. Speed-deceleration lane length curve presents two trends bounded by 200 m, so the speed limit should be in accordance with the deceleration length. Speed-small vehicle curve closing to speed-large vehicle curve presents that the vehicle type is not the factor of the speed limit. After curve fitting and polynomial regression, saturation is considered to be the most influential factor of speed. Speed-saturation prediction model and calibrated speed-limit sign validity model are built through linearization. According to the above results, successive-stage speed limit model is established. An exit ramp was implemented to verify the feasibility and validity of the model.